2022
DOI: 10.1525/elementa.2021.00106
|View full text |Cite
|
Sign up to set email alerts
|

Content in fatty acids and carotenoids in phytoplankton blooms during the seasonal sea ice retreat in Hudson Bay complex, Canada

Abstract: The Hudson Bay complex (HBC) is home to numerous indigenous communities that traditionally have relied heavily on its marine resources. The nutritional quality and stocks of the entire HBC food web depend in large part on the phytoplankton production of bioactive molecules (long chain polyunsaturated fatty acids and carotenoids) and their transfer through trophic levels. The purpose of this study was thus to determine which molecules were produced during spring phytoplankton blooms, as well as the environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 111 publications
1
3
0
Order By: Relevance
“…This is in keeping with reports of salinity and temperature having the greatest influence on the growth rate and biomass accumulation of diverse dinoflagellate species (Kim et al, 2004;Dhib et al, 2013). In a recent study, Amiraux et al (2022) showed that the higher concentrations of dinoflagellates in eastern HB resulted in lower but more diverse content of bioactive molecules being transferred to higher trophic levels. Because the open water season is becoming longer and freshwater inputs are expected to increase in HB, our results suggest heterotrophic groups such as MAST-1A and heterotrophic/mixotrophic dinoflagellates from the Order Peridiniales and Gymnodinales may become more prevalent in summer in coastal HB, with potential influence on the local marine food web.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in keeping with reports of salinity and temperature having the greatest influence on the growth rate and biomass accumulation of diverse dinoflagellate species (Kim et al, 2004;Dhib et al, 2013). In a recent study, Amiraux et al (2022) showed that the higher concentrations of dinoflagellates in eastern HB resulted in lower but more diverse content of bioactive molecules being transferred to higher trophic levels. Because the open water season is becoming longer and freshwater inputs are expected to increase in HB, our results suggest heterotrophic groups such as MAST-1A and heterotrophic/mixotrophic dinoflagellates from the Order Peridiniales and Gymnodinales may become more prevalent in summer in coastal HB, with potential influence on the local marine food web.…”
Section: Discussionsupporting
confidence: 88%
“…Identifying phytoplankton community composition is of concern for inhabitants of Nunavik as local communities consume marine resources, whose quality could be affected by the taxonomic composition of primary producers (Rapinski et al, 2018;Amiraux et al, 2022). Conditions in temperate coastal regions that promote different inshore communities during summer are reasonably well studied and factors leading to different phytoplankton communities include temperature, stratification regimes, intertidal mixing and the extent of allochthonous inputs, which bring in nutrients but can also change light conditions associated with particles and colored dissolved organic material from the land (Peperzak, 2003;Wells et al, 2015;Joli et al, 2018;Boivin-Rioux et al, 2022).…”
Section: Stratification Provides Suitable Habitat For Hab Speciesmentioning
confidence: 99%
“…The Hudson Bay Complex (HBC), consisting of the Hudson Bay, Foxe Basin, James Bay, and Hudson Strait, is a large and shallow (mean depth of 120–150 m, Macdonald & Kuzyk, 2011) subarctic inland sea that experiences seasonal ice cover (Figure 1). The HBC has historically been considered a low‐productivity region in the Canadian Arctic, with the bulk of its chlorophyll a concentration occurring in Hudson Strait, that connects Hudson Bay to the Labrador Sea (1.4 μg L −1 of chlorophyll a in the surface waters and twice as much in the subsurface chlorophyll a maximum in summer; Amiraux et al., 2022) and coastal areas (e.g., up to 2.5 μg L −1 of chlorophyll a in Eastern Hudson Bay; Amiraux et al., 2022; Anderson & Roff, 1980; Bursa, 1961; Ferland et al., 2011; Harvey et al., 1997; Heikkilä et al., 2014). The majority of the measurements reported in these studies have been made in late summer.…”
Section: Introductionmentioning
confidence: 99%
“…Arctic marine food webs are classically viewed as being supported by two ecologically distinct types of primary production, effected in temporal sequence by ice-associated (sympagic) algae in spring and (pelagic) phytoplankton in summer. Each source contributes energy to the ecosystem with varying intensity, community composition, and nutritional quality 1,2 , with phytoplankton typically far more degraded than sea ice algae when it reaches the seafloor. Additionally, the early timing of ice algal blooms and high concentrations of polyunsaturated fatty acids make this a vital resource for many primary consumers in the spring 3 .…”
mentioning
confidence: 99%